2007
DOI: 10.1243/09544119jeim183
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical assessment of the long-term endurance of cemented hip stems. Part 1: Effect of daily activities - a comparison of two load histories

Abstract: The loads during daily activities contribute to fixation failure of cemented hip stems. In-vitro preclinical testing so far has consisted of simulating one or two conditions. Only a small percentage of hip implants fail, with a higher failure rate in most active patients. The goal was to define a procedure to assess the long-term effect of the lifestyle of a reasonably active patient on implant micromotions. Thus, a cyclic load of constant amplitude is unsuitable. All activities inducing high loads were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 57 publications
6
58
0
Order By: Relevance
“…These systems are particularly useful for fatigue studies to quantify migration and inducible motion of the stem, but are not capable of measuring motion at the interface. Drilling through the bone at different locations along the construct and attaching extensometers or LVDT’s provides more information regarding spatial distribution of micromotion [1720]. However the measurements assume that the bone is a rigid body relative to the moving implant.…”
Section: Discussionmentioning
confidence: 99%
“…These systems are particularly useful for fatigue studies to quantify migration and inducible motion of the stem, but are not capable of measuring motion at the interface. Drilling through the bone at different locations along the construct and attaching extensometers or LVDT’s provides more information regarding spatial distribution of micromotion [1720]. However the measurements assume that the bone is a rigid body relative to the moving implant.…”
Section: Discussionmentioning
confidence: 99%
“…This human bone analogue has been widely used to assess stability of stemmed femoral components used in total hip replacement. 12-14 A number of studies have shown the composite femur to be a suitable substitute that replicates the strength and material properties of bone adequately while permitting higher levels of repeatability than their biological equivalent for smaller sample sizes due to the standardised nature of their geometry. 15 Three different femoral components were investigated in this study; a posterior-stabilising (PS), a total-stabilising (TS) implant with short stem (12 mm × 50 mm) and a TS implant with long offset stem (19 mm × 150 mm stem with 4 mm lateral offset), all from the Triathlon series (Stryker, Newbury, United Kingdom) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, as strain is described by a tensor, and displacement by a vector, strain or displacement measurements according to a given direction (which is determined by the sensor itself) are affected by alignment. Therefore, if a transducer is randomly misplaced or misaligned, the readout will suffer from an unpredictable error Cristofolini et al , 2007b). …”
Section: Limitations Of In Vitro Experimentsmentioning
confidence: 99%
“…Different motor tasks need to be simulated to represent the physiological range of loading configurations (O'Connor et al 1996;Heller et al 2001;Cristofolini et al 2007b). In general, such in vitro simulations involve a more complex set-up, often including the action of relevant muscle groups (Cristofolini et al 1995;Duda et al 1998;Cristofolini & Viceconti 1999b;Szivek et al 2000;Stolk et al 2001;Britton et al 2003).…”
Section: Introductionmentioning
confidence: 99%